INVESTIGATING THE STUDENT-TEACHER TECHNOLOGY COMPETENCY FOR ENGLISH LANGUAGE TEACHING: DOES IT MATTER? - Ismail Anas; Akhmad Akhmad (Universitas Islam Negeri Alauddin Makassar, 2020)
The availability of technological tools, the Student and Teacher Technology Competency (STTC) are the essential considerations for the effective use of technology integration in ELT. However, these three aspects are closely interrelated as the key indicators of successful teaching English with technology. This paper reports on the result of an investigation on STTC involving 6 English lecturers and 80 students across the multidisciplinary courses at a vocational higher education setting. The survey is concerned with four domains of technology competencies, they are 1) basic technology operation, 2) personal/ professional use of technology tools, 3) social, ethical, and human issues, and 4) application of technology in instruction (classroom and web-based technology in instruction). This study’s implications call for an inclusion of technological literacy skills in pre-service and in-service EFL teacher professional development programs and education.